Prss55 but not Prss51 is required for male fertility in mice - Kobayashi, Kiyonori (Biol Reprod, 2020)
Mammalian spermatozoa are produced in the testis through spermatogenesis and matured in the epididymis to acquire fertilizing ability. Spermatozoa are ejaculated and migrate from the uterus to the oviducts to fuse with oocytes. Although over 2000 genes are expressed abundantly in mouse testes, the genes responsible for male fertility are not yet fully clarified. Here, we focused on two testis-enriched serine protease genes, Serine protease (Prss) 51 and Prss55, which overlap their gene loci partially in both mice and humans. To characterize their functions in male fertility, we first generated Prss51 and Prss55 double knockout (DKO) mice by CRISPR/Cas9 system and found that the DKO mice were sterile. DKO spermatozoa exhibit impaired migration from the uterus to the oviduct and impaired ability to bind the zona pellucida (ZP) of oocytes. Moreover, a sperm membrane protein, ADAM3 (a disintegrin and metalloprotease 3), which plays a role in sperm migration through uterotubal junction (UTJ) and sperm–ZP binding, disappeared in the DKO spermatozoa from the epididymis. We next generated single knockout (KO) mice lacking Prss51 and found that Prss51 KO mice are fertile. We also generated single KO mice lacking Prss55 and found that Prss55 KO mice phenocopy the DKO mice, demonstrating impaired sperm migration and sperm–ZP binding and a severe defect in fertility. We conclude that Prss55, but not Prss51, is required for male fertility in mice, by stabilizing ADAM3 protein for efficient sperm–UTJ migration and sperm–ZP binding. Our findings have implications for understanding additional genetic causes of the idiopathic male infertility and for the development of male or female contraceptives.